Bacteriological quality and predictors of raw meat collected from municipal slaughterhouse and butcher shops in northeast, Ethiopia - Leykun Berhanu; Adinew Gizeyatu; Masresha Abebe; Daniel Teshome; Mohammed Aragaw; Gete Berihun (Frontiers in Public Health)
BackgroundMeat is a good source of protein in the human diet, and more than three-quarters of the world’s population consumes it. It is the most perishable food item since it has enough nutrients to enable microbial growth. In underdeveloped nations, animals are routinely slaughtered and sold in unsanitary conditions, compromising the bacteriological quality and safety of the meat received from the animals. To protect customers’ health from numerous foodborne diseases this study aimed to determine the microbial quality and predictors of meat along the meat value chain in Northeast, Ethiopia.ObjectiveTo determine the bacteriological quality of meat and its predictors obtained from the Dessie City Administration’s municipal slaughterhouse and butcher shops.Materials and methodsA laboratory-based cross-sectional study design was used. In total 177 meat and 354 swab samples were collected. In addition, 177 meat handlers were randomly selected for knowledge, attitude, and practice assessment. All the samples were analyzed for the presence and counts of total viable count, total coliform count, fecal coliform count, and S. aureus. Multiple linear regression and student T-tests were used to analyze the data. Statistical significance was defined at a p-value of less than 0.05.ResultsThe total viable count of meat samples collected from slaughterhouse and butcher shops were 5.17 ± 0.13 and 6.5 ± 0.87 log CFU/g, respectively. The overall mean total viable count of the meat samples was 5.8 ± 0.1 log CFU/g. Meat samples collected from butcher shops were more highly contaminated than those collected from slaughterhouse. Hand hygiene of meat handlers, the microbial quality of water, and the educational status of meat handlers are all significant predictors of the microbial quality of raw meat along the meat value chain.Conclusion and recommendationThe meat microbial quality is poor and deteriorates along the meat value chain. The hands of meat handlers, the microbial quality of water used to wash the hands of meat handlers, and the educational status of meat handlers significantly affect the microbial quality of raw meat along the meat value chain. Hence, measures should be taken to improve the personal hygiene status of meat handlers and the quality of water used to wash hands and meat contact surfaces.